A Study on the Developments of Financing Policies: supervision of resources by Fundeb’s follow-up and social control council in Paula Freitas/PR - Lucyk, Viviana Patricia Kozlowski (FINEDUCA - Revista de Financiamento da Educação, 2020)
The social control device with the participation of civil society was included in the educational policy from the federal law number 9,424/96, when the Boards of Monitoring and Social Control (CACS) were instituted and the Federal Law number 11,494/2007 sought to improve it. Such device aims to inspect the distribution, transfer and application of Fundeb resources. The present study examined how Fundeb resources are monitored in the city of Paula Freitas/PR. The central objective was to analyze CACS performance in the supervision of Fundeb resources in the mentioned city, through bibliographic and documentary research based in written protocols and laws. It was found that CACS is active in the search for its institutionalization as an instance of social control, but the lack of technical training of its advisors exposes its fragility in supervising Fundeb resources.